Clinicopathological correlation of Cathepsin K expression in salivary gland carcinomas; relation to patients` outcome - Heba Ahmed Elhendawy; Samar Soliman (BMC, 2023)
Abstract Background Salivary gland carcinomas (SGCs) represent various groups of tumors that demonstrate marked diversity in their prognosis owing to different histology and clinical characteristics. One of the poor prognostic indicators is distant metastasis which is considered the major reason for death in SGC patients. Discovering new biomarkers is urgently required to aid in the detection of cancer onset and progression. Cathepsin K (CTSK), the lysosomal cysteine protease has a principal role in cancer invasion and progression through interaction with the tumor microenvironment, degradation of extracellular membrane proteins and destruction of the elastic lamina of blood vessels. In the English literature, little information was present about the role of CTSK in SGCs. The current study aimed to assess the immunohistochemical expression of CTSK in SGCs and correlate its expression to different clinicopathologic parameters. Methods The retrospective study applied to 45 cases of SGCs categorized as high-grade (33 cases) and low-grade SGCs (12 cases) following the criteria of WHO classification (2017) of head and neck tumors. All patients` clinicopathological and follow-up records were retrieved. The following statistical tests were used to study the variance of CTSK expression in SGCs concerning different clinicopathological parameters; Pearson`s Chi-square test, unpaired two-tailed student t-test, One-way ANOVA, and Post Hoc tests. Disease-free survival (DFS) and Overall survival (OS) were calculated and displayed with the Kaplan-Meier strategy and analyzed with the log-rank test. Univariate and multivariate survival analyses were performed with Cox regression. A P-value lesser than 0.05 was considered statistically significant. Results Strong CTSK expression was significantly related to high-grade SGCs (P = 0.000), large infiltrating carcinomas (P = 0.000), presence of nodal (P = 0.041) and distant metastasis (P = 0.009), advanced TNM clinical stage (P = 0.000), the incidence of recurrence (P = 0.009), and reduced DFS (P = 0.006). Distant metastasis was the independent predictor for DFS using Cox regression model. Conclusions CTSK has a great role in cancer progression by triggering many signaling pathways. Its level in cancerous tissue is considered an effective index for predicting the severity and prognosis of cancer. Therefore, we indicate its utility as a prognostic tool and therapeutic target for cancer treatment. Trial registration Retrospectively registered.